DECENTRALIZATION AND THE UNRAVELING OF POWER RELATIONS IN SANGKARRANG ISLANDS, CITY OF MAKASSAR. - Sudarmono Sudarmono (Universitas Padjadjaran, 2023)
How does decentralization provide good public services among traditional fisherfolk and diminish the exploitation of marine resources? This article discusses the positive impact of decentralization on the patron-client relationship of the fishing community by depicting the articulation of social relations and power relations tied among the fisherfolk Sangkarrang Islands, City of Makassar. By employing the theory of access, this study revealed that the proliferation of the Sub District of Sangkarrang had configured the landscape of socio-political interaction. This condition was restructured by the relation of production among producers and successfully eliminated the over-exploitation of marine resources in Sangkarrang Islands. Social hierarchy became more opened and allowed the vulnerable group to access the services provided by the government. They could also channel their political aspiration without being interfered with by a higher social class. At the same time, the political landscape had been rearranged and control from elites tended to be declined. In conclusion, decentralization had increased democratization for local people and had brought public services to be more efficient, including the decreasing of marine exploitation.